The Application of the Student Teams Achievement Division Cooperative Learning Model to the Learning Outcomes of Science in Grade IV - Sinurat, Anselma Nikaria E.; Supriyanto, Supriyanto; Egok, Asep Sukenda (Civiliza Publishing, Indonesia., 2025)
Education is the basis for advancing a country, making education something that must receive serious attention. The purpose of this study is to determine the achievement of the learning outcomes of fourth-grade students of SD Negeri 1 Srikaton in the 2025/2026 academic year after the implementation of the Student Teams Achievement Division Cooperative Learning Model. The research method used in this study is a quantitative approach through the Experimental method. The data collection technique used in this study is the test technique. The data analysis technique used in this study is through the average value and standard deviation, data normality test, and hypothesis test. The results of this study indicate that the average learning outcomes of fourth-grade students of SD Negeri 1 Srikaton after the implementation of the Students Teams Achievement Division (STAD) learning model were significantly completed with a category of more than or equal to 60 (0 ≥60).